The Expenditure Performance and Tax Evectiveness of Kediri Regency - Nasrin, Ewita; Ardini, Mayda Putri; Al-Hasyimi, Muhammad Ilzam Hafidz; Dhiyah, Nazhathul Mila; Rahmawati, Nila Yuni; Viona Caristanica; Hapsari, Mega Tunjung (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
Purpose: The purpose of this study was to determine how the performance of local expenditure and local tax revenue in Kediri Regency. Methodology: The research method used is descriptive-quantitative, using secondary data in the form of financial reports and local government budgets from the Kediri District Statistics Agency and the Ministry of Finance for 2018-2023. Findings: The results showed that Kediri District's expenditure growth for 6 years was classified as unfavorable because the average revenue growth was smaller than the average expenditure growth. Meanwhile, the performance of operational expenditure to total expenditure shows good results because operational expenditure is less than 90%. The performance of capital expenditure on total expenditure also shows good results with a percentage of more than 5%. And the performance of direct expenditure and indirect expenditure on total expenditure shows good results, with the average direct expenditure greater than the average indirect expenditure. In terms of local tax performance, Kediri Regency from 2018-2023 shows very effective results where each ratio value is more than 100%. Novelty: This study analyzes 5 ratios of expenditure performance and local taxes in Kediri Regency for the last 6 years, starting from 2018 to 2023.